Inhibitory Effects of Carbazomycin B Produced by Streptomyces roseoverticillatus 63 Against Xanthomonas oryzae pv. oryzae - Shi, Tingting; Guo, Xin; Zhu, Jiali; Hu, Lingming; He, Zhipeng; Jiang, Donghua (Frontiers in Microbiology, 2021)
Xanthomonas oryzae pv. oryzae (Xoo) causes leaf blight in rice, leading to severe yield losses. In the present study, the biological efficacy of Streptomyces roseoverticillatus 63 (Sr-63) against bacterial leaf blight (BLB) disease was assessed and along with potential mechanism of action. Results demonstrated that the fermentation broth of Streptomyces roseoverticillatus 63 (Sr-63) had remarkable curative activity against BLB. The carbazomycin B isolated from the fermentation broth of Sr-63 was demonstrated to have antibacterial activity against Xoo with the minimum inhibitory concentration (MIC) of 8 μg mL-1. The results indicated that carbzomycin B hampered the membrane formation of Xoo, reduced the production of xanthomonadin and extracellular polymeric substance (EPS). The fourier transform infrared spectroscopic (FT-IR) indicated that the carbazomycin B changed the components of the cell membrane, which caused the change of the cell surface hydrophobicity of Xoo. Scanning electron microscopy revealed that the Xoo cells treated with carbazomycin B exhibited apparent structural deformation. Results also indicated the carbazomycin B had a negative impact on the metabolism of Xoo, the carbazomycin B reduced the activity of malate dehydrogenase (MDH) activity and suppressed the protein expression of Xoo. This study demonstrated that the isolate of Streptomyces roseoverticillatus 63 has potential for use in biological control of Xoo in rice.